Incidence of peritoneal carcinomatosis after perioperative FLOT chemotherapy in gastric cancer. single-center analysis in Kazakhstan - Sarina, Tomiris; Kainazarov, Temirlan; Uskenbayev, Talgat; Burkitbayev, Zhandos; Shalekenov, Sanzhar; Zharlyganova, Dinara; Manatova, Almira; Kuanysh, Zhuldyz; Kerimkulov, Altay (Frontiers in Oncology, 2026)
BackgroundPeritoneal carcinomatosis (PC) significantly impacts prognosis in gastric cancer, limiting survival despite perioperative chemotherapy advancements. The FLOT regimen (5-fluorouracil, leucovorin, oxaliplatin, docetaxel) has become standard for resectable gastric cancer, yet real-world data on PC incidence and clinical impact of PC following FLOT-based treatment, particularly in Central Asia, are limited. This study aimed to evaluate the incidence and clinical implications of PC in a real-world cohort managed with a FLOT-based perioperative strategy in Kazakhstan.MethodsThis retrospective cohort study included 74 with gastric cancer treated at the National Research Oncology Center, Kazakhstan (2020-2024). Patients were planned for perioperative FLOT-based systemic therapy followed by curative-intent surgery, with treatment adaptations reflecting routine clinical practice. Outcomes analyzed were overall survival (OS), relapse-free survival (RFS), and carcinomatosis-free survival (CFS), along with treatment response and patterns of recurrence.ResultsThe cohort was predominantly male (71.6%), with mean age 57.4 years. Most tumors (79.7%) were stage III at diagnosis. One- and two-year OS rates were 87.4% and 70.5%, respectively. RFS rates were 72.0% at one year, decreasing to 53.6% at two years. PC occurred in 50% of relapses, representing the most common recurrence pattern, with median post-progression survival of only 73.5 days. Carcinomatosis-free survival at one and two years was 87.8% and 77.9%, respectively. Prognostic analyses were exploratory due to limited event numbers. Clinical stage was not associated with carcinomatosis-free survival, whereas poorer tumor regression and signet-ring cell histology showed descriptively worse recurrence-free outcomes.ConclusionsPeritoneal carcinomatosis remains a significant challenge following perioperative FLOT chemotherapy in patients with gastric cancer in Kazakhstan, adversely influencing survival outcomes. These findings underscore the necessity for incorporating advanced diagnostic techniques, including peritoneal cytology and improved imaging methods, to enhance early detection and accurate staging. Further prospective studies are warranted to validate these results and develop tailored therapeutic strategies specific to regional healthcare settings.